Tantangan Dan Peluang Kurikulum Merdeka Diera Digitalisasi - Lenny Ristiani; Fadhlya Hidayattul; Fahma Hakim; Merika Setiawati; Nikmah Hayati (Journal Educational Research and Development | E-ISSN : 3063-9158, 2025)
The Merdeka Curriculum is an innovation in Indonesia’s education System that provides flexibility for schools and educators to develop learning according to the needs and potentials of students. The implementation of this curriculum faces various challenges, including the readiness of educators and community support. This article discusses the importance of teacher readiness in applying the Merdeka Curriculum, as well as the role of the community in supporting the learning process. Through collaboration between schools, parents, and society, it is hoped that a more inclusive and adaptive learning environment can be created. This research also highlights strategies that can be implemented to enhance the effectiveness of the Merdeka Curriculum implementation.